Transitioning from globalized to localized and self-reliant economies - Gupta, Ruchika; Srivastava, Priyank, 1979-; Ranjan, Shiv, 1977-; Badar, M. Affan, 1966- (Business Science Reference, 2022)
"With the outbreak of COVID-19 which had a profound impact on global economic growth, this edited book contains contributions that explore the paradigm shift of how economies are moving more toward becoming self reliant"--